A Comparison Between an Individual and a Collaborative Versions of a Serious Game to Learn About Dengue Fever - Buchinger, Diego; Hounsell, Marcelo da Silva (Informática na educação teoria & prática, 2015)
Dengue fever is a major infectious disease caused by arbovirus and there is no vaccine yet; prevention is the action which raises the importance of an educational approach. The use of games to help in the educational process can be motivating and effective but it is not clear which interaction approach is the best: individual or collaborative. A comparative study on a between subject (n=73) experiment using a single player and a pair based version of a serious game that teaches about Dengue fever has been performed. Both versions performed well but presented different advantages: single player version can be used for consulting more easily, and the pair-based game seems to be slightly more motivating to the point that players would be more willing to suggest it to someone else. Data suggest that each interaction approach has its role in the educational process and should be carefully evaluated against educator’s intents.